Modelling and Analysis of Ziegler-Nichols PID Tuning on Water Tank Control System - Regina Chelinia Erianda Putri; Bernadeta Wuri Harini; Iswanjono (International Journal of Applied Sciences and Smart Technologies, 2026)
In the industrial world, the water level in the tank is often controlled using a PID controller. The main problem in using a PID controller is the problem of tuning the three PID parameters (Proportional gain, Integral gain, and Derivative gain). In this study, the parameter controller tuning is done using the heuristic tuning method that is applied on the water level plant and the Ziegler-Nichols tuning method that is simulated using MATLAB software. The results of both tuning methods will be compared. To simulate the control system, the water level system in the tank is modeled in the form of a first-order plus dead time modified with the Pade approach.  Tuning using the Ziegler-Nichols method produced a good response, where the final value of the water level was the same as the set point value (SSE = 0%) with a settling time of 6.18 minutes.